2018
DOI: 10.1111/faam.12162
|View full text |Cite
|
Sign up to set email alerts
|

A balance of strategic management and entrepreneurship practices—The renewal journey of the Swedish Public Employment Service

Abstract: The purpose of this paper is to study the first phase—from 2014 to 2016—of the Swedish Public Employment Service's renewal journey by examining how the agency worked to achieve its new strategy through processes of strategic management and entrepreneurship. We did this through the theoretical lens of strategic entrepreneurship (SE). The results showed that the agency's renewal processes are simultaneously entrepreneurial and strategic. The agency is historically well known for its detailed management and contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 24 publications
2
28
0
2
Order By: Relevance
“…Relating strategic foresight to strategic entrepreneurship, Dogan (2015) showcases strategic entrepreneurship as combination of entrepreneurship (opportunities identification) and strategic management (competitive advantage) significant for organizations to create maximum value, wealth and other benefits as dynamo of development (Kuratko & David, 2008); thus, helping firms to improve and generate sustainable competitiveness and profitability. Hoglund et al (2014) went further to study application of strategic entrepreneurship in an inter-organizational context of both public and private organizations; and confirmed that strategic entrepreneurship motive, has been to keep conditions simple, communicate spillover knowledge, and ascertain flexibility; indicating that though theoretically strategic and entrepreneurial process are construed as opposite, they manifest mutual dependence enabling their existence (Nicolai & Jacob, 2014). However, study pinpoints inadequacy of empirical studies on public organizations like universities pertaining to entrepreneurship, strategic management matters, and inherent consequences (Klein et al, 2013).…”
Section: 1strategic Foresightmentioning
confidence: 92%
“…Relating strategic foresight to strategic entrepreneurship, Dogan (2015) showcases strategic entrepreneurship as combination of entrepreneurship (opportunities identification) and strategic management (competitive advantage) significant for organizations to create maximum value, wealth and other benefits as dynamo of development (Kuratko & David, 2008); thus, helping firms to improve and generate sustainable competitiveness and profitability. Hoglund et al (2014) went further to study application of strategic entrepreneurship in an inter-organizational context of both public and private organizations; and confirmed that strategic entrepreneurship motive, has been to keep conditions simple, communicate spillover knowledge, and ascertain flexibility; indicating that though theoretically strategic and entrepreneurial process are construed as opposite, they manifest mutual dependence enabling their existence (Nicolai & Jacob, 2014). However, study pinpoints inadequacy of empirical studies on public organizations like universities pertaining to entrepreneurship, strategic management matters, and inherent consequences (Klein et al, 2013).…”
Section: 1strategic Foresightmentioning
confidence: 92%
“…Hence, it has been argued that SE practices have a direct effect on organisational performance (Ireland et al 2003;Webb 2007, 2009;Kuratko and Audretsch 2009). In line with this, scholars argue that SE practices are important for both the private (Ireland and Webb 2007;Kyrgidou and Hughes 2010;Luke et al 2011) and public sectors (Höglund et al 2018;Klein et al 2013). SE builds on previous research in entrepreneurship and strategic management, and is described as an interface between two key areas of research that offer new insights into public sector management (Kearney and Meynhardt 2016).…”
Section: Introductionmentioning
confidence: 98%
“…Nevertheless, although entrepreneurship and strategic management over the last three decades are said to be of importance in the public sector (Kearney and Meynhardt 2016), there are few studies available that show how public organisations simultaneously balance strategic and entrepreneurial processes (Klein et al 2013). Notable exceptions are Luke and Verreynne (2006), Klein et al (2013) and Höglund et al (2018), who clearly position their work within SE and explore the practices and possible challenges when introducing SE in the public sector. Most studies of the public sector tend to focus on either strategic management or entrepreneurship, not both, and how entrepreneurial and strategic processes are balanced.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations